Enhancing Electrochemical Performance of LiNi0.6Co0.2Mn0.2O2 by Lithium-ion Conductor Surface Modification. (10th January 2017) - Liu, Siyang; Zhang, Congcong; Su, Qili; Li, Liangyu; Su, Junming; Huang, Tao; Chen, Yanbin; Yu, Aishui
Highlights: An amorphous lithium ion conductor layer was successfully deposited on LiNi0.6 Co0.2 Mn0.2 O2 surface. The concentration of lithium residues on LiNi0.6 Co0.2 Mn0.2 O2 surface was reduced. 1 mol% LLTO modified LiNi0.6 Co0.2 Mn0.2 O2 exhibits excellent electrochemical performance. LLTO coating layer alleviates structure degradation and suppresses interfacial resistance increasing. Abstract: A novel surface modification strategy that could convert lithium residues on the Ni-rich material surface into a lithium ion conductor coating layer was investigated. Various analysis techniques, such as high resolution transmission electron microscopy (HRTEM), energy dispersive X-ray spectrometer (EDS) and X-ray photoelectron spectroscopy (XPS), were used to confirm the formation of an amorphous lithium lanthanum titanate (LLTO) coating layer with a thickness below 10 nm. 1 mol% LLTO modified LiNi0.6 Co0.2 Mn0.2 O2 exhibits the optimized electrochemical performance, with 87.2% capacity retention after 200 cycles at 0.5C, and excellent rate performance compared with that of the pristine LiNi0.6 Co0.2 Mn0.2 O2 . The cycling performance at higher charging voltage (4.5 V) and storage characteristics against moisture and air are also improved significantly after LLTO modification. The enhanced electrochemical performance could be attributed to the high ionic conductivity of LLTO and the uniformity of the coating layer. It can not only suppress the interfacial resistance increasing, but also stabilize the crystal structure of the cathode material during charge-discharge cycling.